The decomposition pathways of C4F7N/CO2/O2 mixtures in the PTFE vapors - Sijie Liu; Xiaolong Li; Zhenxin Geng; Ying Lin (AIP Advances)
The C4F7N/CO2/O2 mixtures have better arc-extinguishing performance compared to the C4F7N/CO2 mixtures, and they have a broader application prospect as a substitute for SF6 in high-voltage circuit breakers and gas insulated substation pipelines. Under high-temperature conditions, the polytetrafluoroethylene (PTFE) vapor produced by insulating materials can affect the decomposition path of the C4F7N/CO2/O2 mixed gas, thereby impacting the arc-extinguishing performance of the mixed gas. This paper conducts quantum chemical calculations based on density functional theory to study the decomposition mechanism of the C4F7N/CO2/O2 mixed gas under the influence of PTFE vapor. This study optimizes the structure of reactants and intermediates and evaluates the energy of molecules using the Gaussian-4 theoretical method. By analyzing the potential energy of the decomposition paths that the C4F7N/CO2/O2 mixed gas may undergo under PTFE vapor, the final decomposition path of the mixed gas under PTFE vapor is obtained. This research can provide a reference for the development of environmentally friendly gases in the study of high-voltage circuit breakers.